DARI BAHASA KE PEMIKIRAN (Serpihan-serpihan Pemikiran Ghazali dalam “Al-Madnu>n bihi ‘ala Ghayr Ahlihi”) - Nuriyadin (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2023)
Abstract: Ghazali was a scholar who was very skilled in the fields of language and literature. He mastered multiple languages and had a deep understanding of Arabic literature. Ghazali's thought from language to thought is an important contribution to the history of Islamic thought. With a holistic approach that combines elements of language, philosophy and religion, it is hoped that it can follow in the footsteps of Ghazali's thinking. Meanwhile, critical and reflective methods are expected to be able to ask and answer critical questions regarding existing understanding in order to achieve deeper and more authentic understanding. As for direct experience and self-introspection, which Ghazali also uses as theory in his studies, it is hoped that he can achieve the truth of real understanding. For Ghazali, academic knowledge alone is not enough to understand the nature of life and religion. In conclusion, Ghazali's thinking from language to thought involves a holistic approach, critical and reflective methods, as well as theories about direct experience and self-introspection. Ghazali's thought had a broad impact in the world of Islamic thought and continues to influence religious thought and practice to this day and language is a symbol of thought itself. Keywords: Language, Ghazali, thought